An update of the Early Cretaceous planktonic foraminiferal biostratigraphy - D. Verga; I. Premoli Silva (University of Neuchatel, 2005)
The first radiation of planktonic foraminifera was thought to begin close to the base of the Aptian. However, recent studies on some Lower Cretaceous successions revealed that this group started to diversify much earlier. Direct correlation with ammonites indicated that the first diversification occurred in the early Valanginian with the appearance of the first hedbergellids, followed by the appearance of the first planispiral form in the late Valanginian. The lowermost Barremian coincided with a remarkable increase both in abundance and number of planktonic species and genera that continued through the Barremian to early late Aptian, accompanied by an overall increase in size. Recent investigations of well-preserved planktonic foraminiferal assemblages of the Barremian through Aptian interval from some successions of Italy, Southern France, Yemen and deep-sea sites drilled off-shore Morocco, allowed to better understanding the morphological features of several taxa that resulted in the reorganisation of the taxonomy of the whole plexus. On the account of the new biostratigraphic data (first and last occurrences) collected in the sections investigated, two new planktonic foraminiferal zones have been identified in the upper Barremian-lower Aptian, while few other zones of the Valanginian-uppermost Aptian “reference” zonal scheme have been re-named. Several taxa do not extend above the Globigerinelloides algerianus Zone and at the close of the Aptian all taxa, especially the larger ones, apparently disappear.